Advancements in Bio‐Integrated Flexible Electronics for Hemodynamic Monitoring in Cardiovascular Healthcare - Ke Huang; Zhiqiang Ma; Bee Luan Khoo (Advanced Science, 2025)
Abstract Cardiovascular diseases (CVDs) remain the leading cause of global mortality, highlighting the urgent need for effective monitoring and prevention strategies. The rapid advancement of flexible sensing technology and the development of conformal sensors have attracted significant attention due to their potential for continuous, real‐time assessment of cardiovascular health over extended periods. This review outlines recent advancements in bio‐integrated flexible electronics designed for hemodynamic monitoring and broader CVD healthcare applications. It introduces key physiological indicators relevant to hemodynamics, including heart rate, blood pressure, blood flow velocity, and cardiac output. Next, it discusses flexible bio‐integrated electronics engineering strategies, such as working principles and configuration designs. Various non‐invasive and invasive bio‐integrated devices for monitoring these hemodynamic indicators are then presented. Additionally, the review highlights the role of artificial intelligence algorithms and their practical applications in bio‐integrated electronics for hemodynamic detection. Finally, it proposes future directions and addresses potential challenges in the field.